Histological Studies on Small Intestine of Giriraj and Bv 300 Layer Breeds of Poultry - Aslam, Sayyed (Indian Journal of Veterinary Anatomy, 2019)
Study was carried out on the comparative histomorphology of small intestine in Giriraj and BV 300 layer breeds of poultry (Gallus gallus domesticus). The villi of tunica mucosa were lined by simple columnar epithelium, with goblet cells, enterocromaffin cells, globular leucocytes. The villi were more in height and finger shaped in the duodenum, beak shaped in jejunum and spatula shaped in ileum in all the age groups of both the breeds. The goblet cells were more numerous in ileum than in duodenum in all age group of both the breeds. The lamina propria was present in the core of villi and around the crypt of  Lieberkuhn. The height of villi in all age groups and width of villi, height of epithelium and height of crypt of Lieberkuhn at 18th week and 52nd week was more in BV 300 layer birds. The width of crypt of Lieberkuhn in all the age groups and width of villi, height of epithelium and height of crypt of Lieberkuhn at the age of 4th week was more in Giriraj birds.